Philosophy for non-philosophers - Althusser, Louis, 1918-1990; Goshgarian, G. M. (London ; New York, NY : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
N 1980, at the end of the most intensely political period of his work and life, Louis Althusser penned Philosophy for Non-philosophers. Available here for the first time in English, Philosophy for Non-philosophers constitutes a rigorous and engaged attempt to address a wide reading public unfamiliar with Althusser's project. As such, the work is a concentration of the most fundamental theses of Althusser's own ideas, and presents a synthesis of his sprawling and disparate philosophical and political writings. Nowhere else does Althusser push the distinction between philosophy and other disciplines as far, or develop in such detail the concept of 'practice'. Rather than a work of 'popular philosophy', Philosophy for Non-philosophers is a continuation and conglomeration of Althusser's thought; a thought whose radicality is still perceptible in those that have followed since. Philosophy for Non-philosophers thus provides a vivid encapsulation of Althusser's seminal influence on the leading thinkers of today, including Ranciere, Badiou, Balibar, and Žižek. -- Provided by publisher.
Acknowledgments -- Introduction by Warren Montag -- Note on the text by G.M. Goshgarian -- Philosophy for Non-Philosophers -- 1. What Non-philosophers Say -- 2. Philosophy and Religion -- The Big Detour -- 3. Abstraction -- 4. Technical Abstraction and Scientific Abstraction -- 5. Philosophical Abstraction -- 6. The Myth of the State of Nature -- 7. What is Practice? -- 8. The Practice of Production -- 9. Scientific Practice and Idealism -- 10. Scientific Practice and Materialism -- 11. Ideological Practice -- 12. The Ideological State Apparatuses -- 13. Political Practice -- 14. Psychoanalytic Practice -- 15. Artistic Practice -- 16. Philosophical Practice -- 17. Dominant Ideology and Philosophy -- 18. Philosophy as Theoretical Laboratory -- 19. Ideology and Philosophy -- 20. Philosophy and the Science of Class Struggle -- 21. A New Practice of Philosophy -- 22. The Dialectic: Laws or Theses?
Includes bibliographical references and index.
Translated from the French.
Keywords: Philosophy -- Introductions